Secular spiritual education - Stephen Bigger (Educational Futures)
Spiritual education and spiritual development are both hotly debated. This conceptual discussion presents spiritual education as referring to personal understanding at its deepest level. It examines and critiques the broad definitions of spiritual education currently proposed, including such aspects as awe and wonder, emotional intelligence, creativity and spiritual intelligence. The article raises concerns about the imposition of doctrinal ‘certainties’ in an education system aspiring to ethical rational inquiry. A new secular model of rational spiritual education is described in which deep personal growth is viewed as the core process of not only spiritual education, but also of general education at its finest.